Linking psychological risk profiles to running-related injuries and chronic fatigue in long-distance runners: A latent profile analysis. (January 2022) - van Iperen, Luuk P.; de Jonge, Jan; Gevers, Josette M.P.; Vos, Steven B.
Abstract: Introduction: Consistently predicting adverse outcomes of long-distance running, such as running-related injuries (RRIs) and chronic fatigue, has proven to be a complicated matter. However, research suggests that a stronger focus on psychological factors of runners might provide further insights. Consequently, in this study, we explored the interplay between self-regulatory coping strategies and motivational aspects. Using a person-centered approach, we investigated whether latent psychological profiles of runners were associated with RRIs and chronic fatigue. Methods: Questionnaire data were gathered from Dutch recreational long-distance runners ( N  = 425) using a cross-sectional design. We determined whether specific psychological combinations (i.e., latent profiles) based on coping strategies (i.e., running-related resources and recovery) and motivational aspects (i.e., harmonious and obsessive passion) could be distinguished using latent profile analysis (LPA). The resulting profiles were tested for their associations with RRIs and chronic fatigue. Results: LPA revealed three different psychological risk profiles, termed the 'low-risk', 'medium-risk', and 'high-risk' profile. The low-risk profile showed low scores on obsessive passion and high scores on all recovery dimensions, whereas the high-risk profile resembled the opposite pattern. Furthermore, the low-risk profile showed significantly fewer RRIs and lower chronic fatigue scores than the high-risk profile. Discussion: The results reveal that (1) patterns of passion and coping strategies interact in defining different profiles and (2) that such profiles are indeed linked to RRIs and chronic fatigue. Utilizing profiles might enable targeted intervention and more effective preventative measures by pinpointing at-risk runners. Specific combinations of psychological aspects, as reflected by our profiles, thus appear a worthwhile direction to consider in understanding RRIs and chronic fatigue in long-distance running. Highlights: We found three psychological risk profiles of long-distance runners: a low-risk, medium-risk, and high-risk profile. Passion for and recovery from running were most important in differentiating these psychological risk profiles. The psychological risk profiles were linked to the risk of running-related injuries and chronic fatigue in long-distance runners.